Kant´s Critique of Pure Reason as a Reform of Metaphysics - Herszenbaun, Miguel (Con-Textos Kantianos. International Journal of Philosophy, 2022)
Review of: de Boer, Karin, Kant’s Reform of Metaphysics. The Critique of Pure Reason Reconsidered, Cambridge, Cambridge University Press, 2020, pp. 280, ISBN 978-1-108-84217-4